Koreanische Frauen in der globalen Ökonomie: Industrialisierung und Geschlechterpolitik in Südkorea - Yoon, Bang-Soon (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The paper analyzes the gender implications of South Korea’s industrialization in terms of women’s employment. Of particular interest is the relationship between women’s educational levels, marital status, and employment patterns as South Korea’s industrialization proceeds. Included in the analysis is the type of South Korea’s industrialization, the role of the state, the role of the local corporate culture, and the impact of the global economy.